2021
DOI: 10.1039/d1ma00304f
|View full text |Cite
|
Sign up to set email alerts
|

Cation disorder and octahedral distortion control of internal electric field, band bending and carrier lifetime in Aurivillius perovskite solid solutions for enhanced photocatalytic activity

Abstract: The overall photocatalytic activity shown by a semiconductor photocatalyst stems from a complex interplay of several critical factors that includes light absorption, carrier recombination dynamics, charge transfer resistance, lifetime of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…It is well known that adsorption of pollutant molecules onto the catalyst surface is a prerequisite for the photocatalytic degradation process and H + ions play a pivotal role in the adsorption of pollutants, in addition to other factors like carrier recombination dynamics, charge transfer resistance and lifetime of photogenerated charge carriers. 78…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that adsorption of pollutant molecules onto the catalyst surface is a prerequisite for the photocatalytic degradation process and H + ions play a pivotal role in the adsorption of pollutants, in addition to other factors like carrier recombination dynamics, charge transfer resistance and lifetime of photogenerated charge carriers. 78…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that adsorption of pollutant molecules onto the catalyst surface is a prerequisite for the photocatalytic degradation process and H + ions play a pivotal role in the adsorption of pollutants, in addition to other factors like carrier recombination dynamics, charge transfer resistance and lifetime of photogenerated charge carriers. 78 To further investigate this, adsorption experiments are carried out with individual RhB at different pH values and with the TC-RhB mixture at acidic pH in the absence of light over Bi 2.5 Sr 1.5 Nb 2 Ti 0.5 M 0.5 O 12 (M = Cr, Mn, Fe) and parent Bi 2 Sr 2 Nb 2 TiO 12 . No adsorption is evidenced in the case of individual TC but surprisingly, adsorption of TC is encountered over all the photocatalysts from the TC-RhB mixture in the acidic medium (Fig.…”
Section: Adsorption and ζ-Potentialmentioning
confidence: 99%
“…Heterojunction systems and composites of Aurivillius perovskites and inorganic compounds or metal–organic frameworks were explored for the removal of enrofloxacin, tetracycline hydrochloride, and Cr (VI) from wastewater to enhance their photocatalytic activity. , Some heterojunction formation between organic and inorganic compounds was also reported previously. , Wang et al reported an organic/inorganic S-scheme heterostructure of TCPP/Bi 12 O 17 Cl 2 for boosting the photodegradation of tetracycline hydrochloride . Dye sensitization is another promising technique for visible-light activation of wide bandgap semiconductors. , On excitation with visible light, the photosensitizer transfers electrons into the semiconductor’s conduction band, which enhances the separation and transportation of photogenerated electrons and holes between the sensitizer and semiconductors .…”
Section: Introductionmentioning
confidence: 85%
“…Photoelectrocatalytic (PEC) water splitting is a clean and viable technology to split water molecules into hydrogen and oxygen using semiconductor photoelectrodes. The overall PEC efficiency of photoelectrodes depends on several factors such as visible light absorption, charge transfer dynamics, and the lifetime of the charge carriers. In PEC water splitting, water oxidation is a sluggish process and is considered a rate-determining step; therefore, the development of a photoanode is a crucial part in PEC water splitting. Mostly, TiO 2 -based photoanodes were investigated in the PEC process due to their availability, stability, and harmlessness, but their wide bandgap (∼3.2 eV) makes them inefficient for harvesting solar energy; therefore, researchers focus on the development of semiconductor materials with a narrow bandgap (<3.0 eV). Recently, bismuth-based semiconductor materials such as BiOX (X = I, Cl, Br) , and Bi x M y O z (M = V, Mo, W, Fe) have attracted a lot of attention in the field of PEC water splitting due to their narrow bandgap, in which the valence band consisting of O-2p and Bi-6s orbitals offers a well-dispersed valence band and facilitates the mobility of the photogenerated holes for water oxidation. Compared to BiVO 4 , Bi 2 MoO 6 and Bi 2 WO 6 have a higher positive valence band edge, and hence, they can expect facile water oxidation by photogenerated holes in PEC water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their bandgap and higher valence band edges than water oxidation, both are considered promising materials for fabrication of photoanodes in PEC water splitting. The unique Aurivillius structure with regular fluorite-like [Bi 2 O 2 ] 2+ layers sandwiched between the perovskite [MoO 4 ] 2– /[WO 4 ] 2– blocks offers the internal electric field to Bi 2 MO 6 (M = W, Mo) and also provides ferroelectricity and a nonlinear dielectric behavior, which improved the charge carrier’s separation. , In addition, the overlapping of the d 0 orbital with filled oxygen 2p orbitals in MO 6 octahedra causes change in the charge distribution among the six oxygen atoms, to overcome this inhomogeneous charge distribution, the metal cation undergoes long-range ordering and cause distortion in MO 6 octahedra, which is called second-order Jahn-Teller distortion (SOJT-D). This intraoctahedral distortion may influence the structural and electronic properties of the materials. The degree of SOJT-D of different metal cations is Mo 6+ ≈ V 5+ ≫ W 6+ ≈ Ti 4+ , based on this, the Bi 2 MoO 6 has a higher magnitude of SOJT-D in MO 6 octahedra than Bi 2 WO 6 .…”
Section: Introductionmentioning
confidence: 99%